The Influence of Person Job Fit and Person Organization Fit on Innovative Work Behavior Through Innovation Trust - Dhillon, Aishwar Shaqilla Kaur; Farisi, Salman (Universitas Pamulang, 2024)
This article aims to determine the influence of a person job fit person organization fit on innovative work behavior through innovation trust as an intervening variable. This research uses a quantitative approach by collecting data through questionnaires. The data analysis technique used in this research is PLS-SEM (Structural Equation Modeling); the population and sample for this research are all employees of PT. Ssaudara Cemerlang Abadi, Medan, North Sumatra, numbering 151. The results of this research show that Person Job Fit has no significant effect on Innovative Work Behavior, Person Organization Fit has a significant effect on Innovative Work Behavior, Person Job Fit has a significant effect on Innovation Trust, Person Organization Fit has a significant effect on Innovation Trust, Innovation Trust has a significant effect on Innovative Work Behavior, Person Job Fit has a significant effect on Innovative Work Behavior, has a significant effect moderated by Innovation Trust, Person Organization Fit has a significant effect on Innovative Work Behavior has a significant effect moderated by Innovation Trust.